Persepsi Nasabah Tentang Mutu Pelayanan dan Produk Bankaltimtara Syariah Cabang Samarinda - Irma Yuliani (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2018)
This study aims to determine customer perceptions of service quality and products of Kaltimtara Sharia Bank Samarinda Branch. This type of research is field research. The nature of this study is qualitative descriptive by using interviews and questionnaires as data collection techniques. The population in this study are all priority customers of Samarinda Bank Kaltimtara Syariah Branch, amounting to 300 customers, using purposive techniques. sampling, the research sample was 75 respondents and interviews with related parties. The results showed that customer perceptions of service quality and products at Bankaltimtara Syariah Samarinda branch were measured using the CARTER dimension (Compliance, Assurance, Reliability, Tangibles, Emphaty, and Responsiveness). Whereas for products measured through 6 dimensions which include Performance, Features, Realiability, Durability, Conformance to specifications and aesthethic shows positive results which are very good but the things that need to be considered are regarding the need for additional park land specialized and financial consultations to meet priority customer needs. This is in line with the results of interviews with relevant parties that indicate the quality or quality of services and products that are sharia standard and in accordance with the vision and mission of Bankaltimtara Syariah.